A production planning Shopwise Araneta Bakery - Collado, Hazel Kristine M.; Diaz, Maria Regina F.; Yumul, Eric Lemuel (Diliman, Quezon City College of Engineering, 2005)
The main objective of the study is to minimize losses that company incurs due to bake-off items' disposals and markdowns. This, the proponents hopes to achieve by recommending the quantities to produce for the bake-off items. Merchandise Acknowledgement Slips, Production Schedules and Daily Sales Reports are gathered and data on quantities produced, disposed, and sold at regular and discounted prices are tabulated from January to early February. Net losses were calculated for each and a Pareto Diagram of the results showed that among the 44 active bake-off items. French Baguette, Mini Ensdaymada, Whole Wheat Dinner Rolls, Superensaymada and Mini Baguettes constitute 80% of the total loss. Thus, these bake off items become the proponents' area of concern. Graphs on quantities sold showed that the demand for the said items depicted that behavior of the demand is a seasonal daily series per week with no trend. It was also noted that peak sales happen on Saturdays and Sundays. Using the stationary series technique of forecasting, estimates of the demand for the items were calculated. Safety stock levels are then obtained to be added in the forecasted results. This was done to prevent running out of stocks, hence assuring higher service levels. The single period model was used here since baked goods are perishable goods. Adding these safety stocks, the proponents recommend that the following quantities be produced for the above mentioned items for Monday to Sunday: Mini Baguette-13,13,12,14,14,23,23; Sweet Dinner Rolls-13,15,15,16,17,30,33; Mini Ensaymada-324,336,360,378,492,292; Whole Wheat Dinner Rolls-52,51,56,54,54,70,67; Super Ensaymada-50,48,42,45,49,76,79. Scheduling of the items was also done by determining the sequence by which the items should be processed. Johnson's algorithm was used since set up times are constant, and is therefore independent of the sequence used. Results show that to minimize make span, the items should be processed in this sequence.: Nut Caramel Loaf, Raisin Bread, Butter Zopf, multi-Grain, Oatie Bran, Rye, Sesame Bread, Carrot Bread, Whole Wheat Bread, Cove Bread, Easy Veggie, Foccacia, Onion Bread, Potato, Pumpkin, Sweet Dinner Rolls, Cluster Loaf, Superensaymada, Cinammon with Apple, Cinammon Roll, French Baguette, Mini Baguette, Whole Wheat Baguette, all pandesal, Cheese Breadm Hamburger Buns, Hotdog in a Bun, Mini Cinammon Roll, Mini Cinammon Roll with Apple and Mini Ensaymada. Also, the proposed sequence proves to be better in terms of oven capacity utilization. With the recommendations stated above, the group hopes to help the company in achieving its goals by reducing losses and improving system operations.
Feasibility study
Submitted in partial fulfillment of the course requirements in IE 151 : Production Systems
Keywords: Shopwise Araneta Bakery; Bread industry; Production engineering